(untitled) (Texas Journal of Medical Science, 2022)
The COVID -19 pandemic is creating completely new and unexplored challenges for patients and healthcare around the world. The severe course of the disease, including lung damage, requires various types of respiratory support both in the intensive care unit and in the clinical infectious diseases departments [1, 2]. The main risk group, in which there is a high incidence of adverse outcomes and a higher mortality rate, are the elderly, persons with severe concomitant comorbidities, as well as patients with protein - energy malnutrition. Dependence on respiratory support, a pronounced immune response of the body, comorbidities, advanced age are usually associated with a high risk of developing malnutrition, which in itself is a risk factor for the development of additional infectious and inflammatory complications, an increase in the time spent on respiratory support, in the intensive care unit and intensive care unit. therapy in the hospital.